Pengaruh Latihan Kelincahan Dan Latihan Kecepatan Terhadap Peningkatan Dribble Pada Siswa Ekstrakurikuler Futsal SMA Negeri 3 Palopo - Unco Prasetyo Rahim; Nur, Suaib; Hajeni, Hajeni (Jurnal Porkes, 2025)
The background of this study is the importance of dribbling techniques in futsal, but the basic dribbling skills of futsal extracurricular students at SMAN 3 Palopo are still not optimal. This study aims to determine the effect of agility training and speed training on improving dribbling skills, as well as comparing the effectiveness of the two training methods. The method used was a quantitative experiment with a two group pretest-posttest design. The sample consisted of 20 students divided into two groups: group A was given agility training (zig-zag run) and group B was given speed training (shuttle run), each for 16 sessions. The research instrument used a dribbling test. The data were analyzed using normality, homogeneity, paired sample t-test, and independent sample t-test. The results showed that both agility and speed training had a significant effect on improving dribbling (p < 0.05). However, the independent sample t-test proved that agility training was significantly more effective than speed training. The conclusion of this study is that although both exercises are effective, agility training has a greater impact on improving students' futsal dribbling skills. These findings recommend that coaches prioritize agility training in dribbling technique development programs.